Marine Sustainable Yield Analysis of Pelagic Fisheries in Sea Based on Catch Landing data From Tumumpa Fishery Harber, Manado North Sulawesi - Rumambi, David Y; Rembet, Unstain N. W. J.; Sangari, Joudy R. R. (Jurnal Ilmiah PLATAX, 2018)
This research activity took place in Manado City, North Sulawesi Province with activities centered on the Tumumpa Fishery Harbor (PPP). The data were recorded from capture fisheries activity conducted in the Sulawesi Sea and its surroundings landed in the Tumumpa Fishery Harbor. The purpose of this study was to analyze the stock value and Maximum Sustainable Yield (MSY) of pelagic fish in the Sulawesi Sea based on the approach of the surplus production model (Model Schaefer). This research is expected to be used as a consideration in the management of pelagic fish stocks in the Sulawesi Sea, and can be used as a basis for further research. This research uses secondary data collection method in the form of statistical document and record available. The data taken, including fish catch and fishing effort or effort (trip), from 2012 to 2016 (5 years). The results show that production value is inversely proportional to the value of effort, where the value of production from 2012 to 2016 has decreased every year, while the value of effort from 2012 to 2016 has increased. This condition indicates that the presence of pelagic fish stocks in the Sulawesi Sea and surrounding areas has been and is experiencing a decline that impacts on the decrease of production every year with a large percentage and this condition also indicates the occurrence of potentially overfishing. The value of MSY utilization of capture fishery resources in the Sulawesi Sea based on Tumumpa Fishery Harbor data were 16,305.45 tons / year for HMSY and 1,664,59 trips / year for EMSY, with TAC of 13,044.36 tons / year.Keywords : Capture fishery, MSY, Pelagic, Surplus Production Model, Tumumpa ABSTRAK Kegiatan penelitian ini berlangsung di Kota Manado, Provinsi Sulawesi Utara dengan kegiatan berpusat di Pelabuhan Perikanan Pantai (PPP) Tumumpa Manado. Aktivitas perikanan tangkap yang ditelaah berlangsung di kawasan perairan Laut Sulawesi dan sekitarnya berdasarkan data PPP Tumumpa Manado. Tujuan dari penelitian ini adalah untuk menganalisis nilai stok dan Maximum Sustainable Yield (MSY) ikan pelagis di Laut Sulawesi berdasarkan pendekatan model produksi surplus (Model Schaefer). Penelitan ini diharapkan dapat digunakan sebagai bahan pertimbangan dalam pengelolaan stok ikan pelagis di Laut Sulawesi dan sekitarnya, serta dapat digunakan sebagai dasar untuk penelitian selanjutnya. Penelitian ini menggunakan metode pengumpulan data sekunder berbentuk dokumen. Data yang diambil adalah data tangkapan ikan dan upaya penangkapan ikan atau effort (trip), dari tahun 2012 sampai dengan 2016 (5 Tahun). Hasil penelitian menunjukkan nilai produksi berbanding terbalik dengan nilai effort, di mana nilai produksi dari tahun 2012 sampai 2016 mengalami penurunan setiap tahunnya, sedangkan nilai effort dari tahun 2012 sampai tahun 2016 mengalami peningkatan. Kondisi yang terjadi ini mengindikasikan bahwa keberadaan stok ikan pelagis di Laut Sulawesi dan sekitarnya telah dan sedang mengalami penurunan yang berdampak pada penurunan produksi setiap tahun dengan persentase yang cukup besar di mana kondisi ini mengindikasikan terjadinya overfishing. Nilai MSY pemanfaatan sumber daya perikanan tangkap di Laut Sulawesi berdasarkan data PPP Tumumpa Manado sebesar 16.305,45 ton/tahun untuk HMSY, dan 1.664,59 trip/tahun untuk EMSY, dengan TAC sebesar 13.044,36 ton/tahun.Kata Kunci: Perikanan Tangkap, MSY, Pelagis, Model Produksi Surplus, Tumumpa